PERFORMANCE ANALYSIS OF ELECTRIC VEHICLE CONVERSION AT CENTER OF GRAVITY MEASUREMENT - F. Zainuri; D. A. Sumarsono; Mohammad Adhitya; I. Wahyudi; I. Choiri; A. Azis; G. Fauzan; M. Triananda; F. Arrafi; F. A. Falah (Sekolah Tinggi Teknologi Wastukancana, 2020)
In this study, the conversion is done by changing conventional gasoline-powered vehicles with electricity. Replacement is done by removing the drive engine and replacing it with a drive motor that is automatically added to the battery as an energy source. Laying the existing components affects the center of grafity where all car weights are centered in one meeting point. The car that we usually see on the road has a lot of heavy components, such as engine blocks, pistons, batteries, gearboxes, axles, transfer cases and heavy components scattered throughout the car, so naturally there is a